The genus Gelanes Horstmann (Hymenoptera: Ichneumonidae: Tersilochinae) from South Korea, with description of four new species - Kim, Ki-Beom; Balueva, Ekaterina N.; Khalaim, Andrei I.; Lee, Jong-Wook (Zootaxa, 2013)
The genus Gelanes Horstmann is recorded from South Korea for the first time. Eight species of the genus are found to occur in this country. Four species, G. dentator sp. nov., G. protritus sp. nov., G. provectus sp. nov. and G. verendus sp. nov., are described as new, three species, G. belokobylskii, G. cuspidatus and G. simillimus, also occur in the Russian Far East, and G. gubarevae was previously known only from Europe. A key to the South Korean species of Gelanes is provided.